Introduction to Apache Hive : quickly create and query large datasets with SQL in Hadoop - Hanlon, Tom (O'Reilly, 2015)
"In this Introduction to Apache Hive training course, expert author Tom Hanlon will teach you how to create and query large datasets in Hadoop. This course is designed for the absolute beginner, meaning no experience with SQL or Hadoop is required. You will start by learning how to connect to Hive, then jump into learning how to create tables and load data. From there, Tom will teach you how to manipulate tables with HiveQL, including how to insert data into a Hive table using HiveQL. This video tutorial also covers how to create views and partitions and transform data with custom scripts. Finally, you will learn about Hive execution engines, such as Map Reduce, Tez, and Spark. Once you have completed this computer based training course, you will have learned how to create tables and load data in Hive, execute SQL queries, use user defined functions, and transform scripts."--Resource description page.